Carrying Capacity of Tepian Batu Lake Siak Hulu Sub District Kampar District Riau Province Based on Dissolved Oxygen - Astria, Katarina Gita; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractCarrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. A study aimed to determine the aquatic carrying capacity for aquaculture fishing. The carrying capacity was determined based on dissolved oxygen concentration. The research was conducted during June to July 2019 in Tepian Batu Lake. Water samples were taken in three stations, namely Station 1 (inlet area), Station 2 (middle of the lake), and Station 3 (the end of the lake).In each station there were 2 sampling sites, namely surface and in the 2 Secchi depth. Sampling was done four times, once/week. Water quality parameters measured were dissolved oxygen, temperature, transperancy, pH, carbondioxide. nitrate and phosphate concentration. Carrying capacity was analyzed using the Kartamihardja formula (1998). Result shown that DO concentration 3.96-5.36 mg/L at the surface; 3.13-4.37 mg/L at water column. Water quality parameters were as follows: transparency ranges from 56.5-63.75 cm, temperature 28.75-30.5oC, pH 5-5.5, carbondioxide 6-12 mg/L, nitrate 0.031-0.078 mg/L and phosphate 0.062-0.116 mg/L. Carrying capacity of Tepian Batu Lake is 1276 kg/year and number units can be operated is 12 units. The current number of floating cages (FNC) unit in Tepian Batu Lake is 25 units. Based on data obtained that number of floating cages in Tepian Batu Lake has exceeded the carrying capacity. Keywords : Carrying capacity, dissolved oxygen, and floating cages